Comparison of Student’s Learning Outcomes in Mathematics Subjects Using STAD Type Cooperatives with Peer Tutors in Grade X of SMA PGRI Betung Kabupaten Banyuasin - Natalia, Tri (PPSDP International Journal of Education, 2024)
The learning model used is still teacher-cantered, this makes students tend to be passive in following the learning process in class, so that student learning outcomes are relatively low. To overcome this, there are many learning models that can improve student learning outcomes and require students to be active. in participating in learning activities. One of the researchers tried to use the STAD Type Cooperative learning model and Peer Tutor. The aim of this research was to find out which was better. The learning outcomes of students using the STAD Type Cooperative compared to those using Peer Tutors in class X SMA PGRI Betung, Banyuasin Regency. The population of this study were all class X students of SMA PGRI Betung, Banyuasin Regency. The samples were taken from two classes, namely classes X1 and X3, using simple random sampling techniques. The method used in this research is the experimental method. The data collection technique that the researcher carried out was a test technique and to analyse the data, statistical analysis was carried out using the t test. The results of the data analysis, which are strengthened by the results of the evaluation test data analysis, prove that the learning outcomes achieved by students in mathematics subjects using STAD Type Cooperative are better than the learning outcomes achieved by students in mathematics subjects using Peer Tutors.